Ruang KAP (Komunikasi Antar Pribadi) Sebuah Program Untuk Peningkatan Kapasitas Para Kader Kesehatan - Faridah; Ishanan; N.Rohmah, Nurliya (LP2M Universitas Islam Ahmad Dahlan, 2024)
Public awareness of the polio vaccine for toddlers in the Mataram area in 2023 is still at 30.2%, or 2,645 children (the lowest in NTB). To address this issue, behavior change intervention components must be further developed. In the context of field communication, health cadres need to be equipped with more innovative communication techniques as the front line. For this purpose, continuous training such as the Training of Communicator (ToC) with an Interpersonal Communication Approach (KAP) needs to be provided to health cadres to enhance their communication skills and medical knowledge. The goal of this service is to equip cadres with techniques to build closer, trusting, and understanding relationships to facilitate educating and persuading residents, to provide cadres with techniques for explaining immunization issues in ways that are easily understood by the general public, and to equip cadres with techniques to lock in commitment and build habits so that long-term behavior change can occur. The success rate of the service activity is 90%, based on the KAP method indicators of participant engagement at every step and happiness during the training. This can be observed from the beginning of the training in the morning until the end, with health cadres always laughing and not feeling sleepy or weak. They are also committed to taking action with KAP in the community. They returned home smiling and expressed gratitude for the communication knowledge imparted